A Two-dimensional Mixed Baseline Method Based on MIMO-SAR for Countering Deceptive Jamming - ZENG Zheng; ZHANG Fubo; CHEN Longyong; BU Xiangxi; ZHOU Siyan (Leida xuebao, 2019)
A novel approach using two-dimensional mixed baseline based on Multi-Input Multi-Output Synthetic Aperture Radar (MIMO-SAR) has been proposed for range delay and azimuth Doppler frequency modulation used in deceptive jamming. Based on MIMO-SAR phase coding method, which makes the multichannel signal orthogonal, we propose the detection of deceptive jamming phenomenon by employing multidimensional phase information, and suppress the jamming targets via phase compensation to improve the ability of countering deceptive jamming. Moreover, we utilize radar anti-jamming improvement factor as a quantitative evaluating index. In the limited platform space, the radar anti-jamming improvement factor of the proposed method is three times greater than that of conventional single-input multi-output systems. Experimental results demonstrate the validity of our method.